1996
DOI: 10.1029/96jd01549
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term observation of nitrate radicals at the Tor Station, Kap Arkona (Rügen)

Abstract: Long-term observation of the trace gases NOa, ozone, and nitrate radicals (NO3) at a rural site in the Baltic Sea (near Kap Arkona, island Riigen) using differential optical absorption spectroscopy (DOAS) are presented here. The time series of these species cover more than 14 months of data. Additionally, meteorological data were taken from the Deutscher Wetterdienst station at Kap Arkona. The average nighttime NO3 concentration was determined at 7.8 ppt. Maximum lifetimes of more than 5000 s were observed, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
147
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(164 citation statements)
references
References 60 publications
15
147
2
Order By: Relevance
“…The mean nighttime value of 25 k OTG was ≈ a factor ten lower at 0.11 s -1 , the daytime mean even lower at 0.04 s -1 . Broadly speaking, the nighttime NO 3 lifetimes during IBAIRN were very short (≈ 10 s on average) compared to previous indirect, ground level measurements in other locations where several groups have reported lifetimes of hundreds to thousands of seconds (Heintz et al, 1996;Allan et al, 1999;Geyer et al, 2001;Aldener et al, 2006;Ambrose et al, 2007;Brown et al, 2009;Crowley et al, 2010;Crowley et al, 2011;Sobanski et al, 2016b Figure 3b illustrates the dependence of k OTG on wind direction. Air masses from the northern sector were generally associated with lower reactivity (<0.2 s -1 ) whereas all incidents of reactivity larger than 0.3 s -1 were associated with air masses from the SE sector.…”
Section: No 3 Reactivity and Nighttime Loss Of Omentioning
confidence: 80%
“…The mean nighttime value of 25 k OTG was ≈ a factor ten lower at 0.11 s -1 , the daytime mean even lower at 0.04 s -1 . Broadly speaking, the nighttime NO 3 lifetimes during IBAIRN were very short (≈ 10 s on average) compared to previous indirect, ground level measurements in other locations where several groups have reported lifetimes of hundreds to thousands of seconds (Heintz et al, 1996;Allan et al, 1999;Geyer et al, 2001;Aldener et al, 2006;Ambrose et al, 2007;Brown et al, 2009;Crowley et al, 2010;Crowley et al, 2011;Sobanski et al, 2016b Figure 3b illustrates the dependence of k OTG on wind direction. Air masses from the northern sector were generally associated with lower reactivity (<0.2 s -1 ) whereas all incidents of reactivity larger than 0.3 s -1 were associated with air masses from the SE sector.…”
Section: No 3 Reactivity and Nighttime Loss Of Omentioning
confidence: 80%
“…After sunset, the isoprene mixing ratio drops rapidly, and it has been suggested that the reaction with nitrate radicals, NO 3 , is a major contributor to isoprene decay at night (Curren et al, 1998;Starn et al, 1998;Stroud et al, 2002;Steinbacher et al, 2005). Typical NO 3 radical mixing ratios in boundary layer continental air masses range between ∼10 to ∼100 ppt (Platt and Janssen, 1995;Smith et al, 1995;Heintz et al, 1996;Carslaw et al, 1997). However, concentrations as high as…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, OH was neglected during the night and NO 3 during the day [e.g., Armerding et al, 1997;Atkinson, 2000;Crosley, 1997;Eisele et al, 1997;Finlayson-Pitts and Pitts, 2000;Fuentes et al, 2000;Kleinman, 2000;Logan et al, 1981;Monks et al, 1998;Platt, 1991;Wayne et al, 1991;Weaver et al, 1996]. In fact, OH and NO 3 measurements were often paused during nighttime and daytime, respectively [e.g., Allan et al, 1999;Brune et al, 1995;Geyer et al, 2001a;Hard et al, 1995;Heintz et al, 1996;Holland et al, 1998;Mount et al, 1997;Platt et al, 1981]. Today it is becoming clear that this separation is not generally valid.…”
Section: Introductionmentioning
confidence: 99%